Hypoxia-inducible factor-2α plays a role in mediating oesophagitis in GORD. Issue 9 (30th September 2016) - Huo, Xiaofang; Agoston, Agoston T; Dunbar, Kerry B; Cipher, Daisha J; Zhang, Xi; Yu, Chunhua; Cheng, Edaire; Zhang, Qiuyang; Pham, Thai H; Tambar, Uttam K; Bruick, Richard K; Wang, David H; et al.
Abstract : Objective: In an earlier study wherein we induced acute reflux by interrupting proton pump inhibitor (PPI) therapy in patients with reflux oesophagitis (RO) healed by PPIs, we refuted the traditional concept that RO develops as an acid burn. The present study explored our alternative hypothesis that RO results from reflux-stimulated production of pro-inflammatory molecules mediated by hypoxia-inducible factors (HIFs). Design: Using oesophageal biopsies taken from patients in our earlier study at baseline and at 1 and 2 weeks off PPIs, we immunostained for HIF-1α, HIF-2α and phospho-p65, and measured pro-inflammatory molecule mRNAs. We exposed human oesophageal squamous cell lines to acidic bile salts, and evaluated effects on HIF activation, p65 function, pro-inflammatory molecule production and immune cell migration. Results: In patient biopsies, increased immunostaining for HIF-2α and phospho-p65, and increased pro-inflammatory molecule mRNA levels were seen when RO redeveloped 1 or 2 weeks after stopping PPIs. In oesophageal cells, exposure to acidic bile salts increased intracellular reactive oxygen species, which decreased prolyl hydroxylase function and stabilised HIF-2α, causing a p65-dependent increase in pro-inflammatory molecules; conditioned media from these cells increased T cell migration rates. HIF-2α inhibition by small hairpin RNA or selective small molecule antagonist blocked the increases in pro-inflammatory molecule expression and T cell migration induced by acidic bile salts. Conclusions: In patients developing RO, increases in oesophageal HIF-2α correlate with increased pro-inflammatory molecule expression. In oesophageal epithelial cells, acidic bile salts stabilise HIF-2α, which mediates expression of pro-inflammatory molecules. HIF-2α appears to have a role in RO pathogenesis. Trial registration number: NCT01733810 ; Results.